THE URGENCY TO STRENGTHEN THE INTEGRATION OF THE INDONESIAN BORDER AGENCIES TO REDUCE CASES OF ILLEGAL IMMIGRANTS - Sania Nizar Putri Ashari; Wisnu Widayat (Journal of Law and Border Protection, 2020)
The opening of access to national borders in globalization era in the context of global level cooperation has caused many foreign citizens to migrate to other countries. Thus, various threats of crime and criminal acts are a challenge that must be given more attention, because state borders also involve state sovereignty and the security of a country. Likewise with Indonesia which borders many countries, making Indonesia vulnerable to the problem of illegal immigrants entering the territory of the country. Illegal immigrants are a definite threat because they have the potential to commit crimes, drug trafficking, people smuggling, prostitution, and even other crimes.Indonesia has various kinds of institutions that have the authority to guard borders, such as the Police, the Indonesian National Army, Immigration, and the Maritime Security Agency of the Republic of Indonesia, in practice these border control agencies carry out their respective duties and functions, and until 2020 various collaborations have been carried out. between these institutions in carrying out their duties, however, cases of illegal immigrants are still widely found and occur on the Indonesian border, so that the urgency to strengthen the integration between the border supervisors to maximize supervision of the Indonesian border does indeed exist and must be realized immediately.